To Determine the Frequency of Pyrexia in Women with Prelaborrupture of Membranes - Maimoona Qadir; Sohail Amir (Gandhara University, 2017)
OBJECTIVE To determine the frequency of pyrexia in patients with prelabor rupture of membranes METHODOLOGY This descriptive (cross sectional) study was conducted in Department of Gynecology and Obstetrics, Khyber Teaching Hospital, Peshawar from 12th January 2016 to 13th July 2016.Sample size was 369,keeping 4% proportion of pyrexia among women with PROM,95% confidence interval and 2%margin of error under WHO sample size calculation. All women with any age or parity who presented with prelabor rupture of membranes were included in the study. RESULTS In this study, 369 women with PROM were observed.41(11.1%) patients were less than 20 years,139(37.7%) were in 21-30years age range,179(48.5%) were in age group 31-40years and only 10(2.7%) were more than 41 years age. Average age was 29.53+6.3SD.The pyrexia among women with PROM was observed in 39(10.57%)women, being more common in 31-40 years age group where it was noticed in 20(11.2%),followed by 21-30years age where 14(10.1%)patients were pyrexial. CONCLUSION Pyrexia is an enormous public health problem, accounting for the majority of cases of PROM in this part of the country.